2014
DOI: 10.1021/ie403544d
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Acrylamide/N,N′-Methylenebisacrylamide Solution Copolymerization

Abstract: A model of free-radical crosslinking copolymerization in solution, based on Flory's gelation theory and developed by Tobita and Hamielec [Macromolecules, 1989, 22, 3098-3105] has been applied to the system acrylamide/ N,N'-Methylenebisacrylamide. The evaluation of missing rate constants was performed by comparing model predictions with experimental measurements of swelling ratios and literature data. This way, the interplay of crosslinking and intramolecular cyclization reactions, regulating the network forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The polymer network prepared in the presence of solvent has a loose network whereas that of prepared in bulk conditions has a tight structure including interpenetrated network chains. Since the synthesis process of the Hgs includes a high degree of complexity, the modeling and optimization approaches have been developed based on the simulations as well as neural networks to define the nature of the polymerization process where an understanding of the gelation phenomenon is limited . Curteanu and coworkers reported that the artificial neural networks can be used to make predictions for the synthesis of a one‐pot process of PAAm‐based Hgs, especially emphasizing some possibilities of theoretical study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymer network prepared in the presence of solvent has a loose network whereas that of prepared in bulk conditions has a tight structure including interpenetrated network chains. Since the synthesis process of the Hgs includes a high degree of complexity, the modeling and optimization approaches have been developed based on the simulations as well as neural networks to define the nature of the polymerization process where an understanding of the gelation phenomenon is limited . Curteanu and coworkers reported that the artificial neural networks can be used to make predictions for the synthesis of a one‐pot process of PAAm‐based Hgs, especially emphasizing some possibilities of theoretical study.…”
Section: Resultsmentioning
confidence: 99%
“…Since the synthesis process of the Hgs includes a high degree of complexity, the modeling and optimization approaches have been developed based on the simulations as well as neural networks to define the nature of the polymerization process where an understanding of the gelation phenomenon is limited. 41,42 Curteanu and coworkers 43 reported that the artificial neural networks can be used to make predictions for the synthesis of a one-pot process of PAAmbased Hgs, especially emphasizing some possibilities of theoretical study. Neural networks including five inputs; the concentrations of monomer, initiator, crosslinking agent, temperature, and time and corresponding two outputs; the polymer yield and the swelling degree were designed to test several topologies and to identify the reaction conditions which lead to an imposed reaction yield or a maximum swelling degree.…”
Section: Influence Of the Monomer Concentration On Equilibrium Swellimentioning
confidence: 99%
“…estimated that 95% of the PDBs underwent primary cyclization if the solid weight fraction was 5%. The primary cyclization is influenced by chain flexibility, primary chain length, and solvent quality, apart from the weight fraction of the monomer …”
Section: Resultsmentioning
confidence: 99%
“…Primary intramolecular cyclization is initiated by one double bond and one radical in a propagating chain, and it would result in a loop structure which does not contribute to the mechanical properties of the hydrogel . Primary intramolecular cyclization is independent of the crosslinking agent concentration but is dependent on the total monomer concentration …”
Section: Introductionmentioning
confidence: 99%
“…For the synthesis of ion exchangers, the suspension copolymerization of acrylonitrile (AN) with crosslinking agents is widely used [2,3]. Acrylonitrile ionites are obtained with crossing it with hexamethylenedimetalacrylamide, diallylftalatte, divinylbenzene (DVB), N,N-methylene-bisacrylamide (MBA), hexagidro-1,3,5-triacrylotriazine (GTT), etc [4][5][6][7]. In the literature, many are described synthesis and study of acrylonitrile copolymers with various crosslinking agents, aimed at obtaining ion exchangers for various cations and anions [2, [8][9][10][11][12],…”
mentioning
confidence: 99%